KELAYAKAN KULIT JERUK MANIS (CITRUS SINENSIS) SEBAGAI HAIR TONIC PERAWATAN RAMBUT RONTOK - Julita, Nova Julita (Journal of Beauty and Cosmetology (JBC), 2023)
Hair loss can occur physiologically or pathologically influenced by factors from inside and outside the body. Hair loss is caused by heredity and hormonal influences. Sweet Orange Peel (Citrus Sinensis) is a plant that can be used as a fertilizer and accelerate hair growth. Therefore the purpose of this study is to analyze the feasibility of sweet orange peel as hair tonic, to analyze the feasibility of sweet orange peel hair tonic seen from laboratory tests (content of vitamin C and Flavonoid), physical tests (absorption), organoleptic tests (odor and color), and hedonic tests (preference of researchers). This a study that combined an experimental design with quantitative research tools, the free variable in this study was sweet orange peel as hair tonic. The dependent variables in this study are the test of Flavonoid and Vitamin C content and absorbency test, organoleptic test of finished hair tonic results including color, aroma and hedonic test, which is the preference of panelists. The data collection techniques used are observation methods, documentation and observation sheets. The results of the study obtained from the flavonoid content test using concentrated HCL peraksi and Mg powder were negative, and the vitamin C content test using iodine peraxium and the results were positive. It is expected that for the Department of Cosmetology and Beauty FPP UNP, research on the feasibility of sweet orange peel as a hair tonic for hair loss treatment can be used as a reference in future research and can be refined.